Korelasi Mata Kuliah Kewirausahaan dengan Motivasi Wirausaha Mahasiswa Bidang Kelistrikan - Adma Gumalta Riski; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to determine the relationship between entrepreneurship courses and entrepreneurial motivation in the electrical sector. The subjects in this study were students of the 2017 State University of Padang Electrical Engineering Education Study Program with a total of 45 respondents. This type of research is a quantitative research with correlational method. Data collection was carried out by distributing questionnaires to students through WhatsApp groups and personal chats. Before distributing the research instrument, the research questionnaire was validated by two expert lecturers first. After being validated by expert lecturers, the next step is instrument testing. The data analysis used is validity test and reliability test to test the research questionnaire instrument. The trial was conducted on students of the 2018 State University of Padang Electrical Engineering Education Study Program with a total of 30 respondents. Furthermore, the normality test and linearity test as a prerequisite test for correlation analysis. Then the correlation test was carried out to determine the value of the correlation coefficient between the two variables using the correlational product moment formula. The results of the calculation of the hypothesis test in this study indicate that the entrepreneurship course has a significant relationship with entrepreneurial motivation in the electricity sector. The results of the analysis also show that entrepreneurship courses have a moderate level of closeness with entrepreneurial motivation in the electricity sector.